Effect of Different Stock Densities on Growth and Lifetime of Red Tilapia (Oreochromis niloticus) that are Maintained by Bioflok Technology - Septibelavitta Simangunsong; Iskandar Putra; Rusliadi Rusliadi (Jurnal Akuakultur SEBATIN, 2023)
This research was carried out in December 2020-January 2021 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Affairs, University of Riau. The purpose of this study was to determine the effect of stocking density of red tilapia reared with biofloc. The method used in this study was an experiment with a completely randomized design (CRD) one factor four experimental levels three times. The treatments carried out were different stocking densities of red tilapia with treatments that were P1 16 fish/80 L, P2 24 fish/80 L, P3 32 fish/80 L, P4 40 fish/80 L. The best was found in P4 40 tails/80 L with an average weight of 6.63 g, Absolute Weight Growth 5.67 g, Specific Growth Rate 4.83%/day, Average Length Growth 7.95 cm, Absolute Length Growth 4.16 cm, Feed Conversion Ratio 0.93, Feed Efficiency 107.55%, Survival Rate 88.33%, and water quality parameters such as temperature 27-30 OC, pH 5-6, DO 7.5-8.2 mg/L and NH3 0.009-0.035 mg/L